Development of rainfall intensity Nomograph for Kolhapur station (Maharashtra) - BARAI, V. N.; KSHIRSAGAR, R. K. (Journal of Soil and Water Conservation, 2020)
The study was undertaken to update the constants of rainfall intensity â€“ duration â€“ return period relationship and Nomograph by using data of rainfall charts from 1989 â€“ 2014 for Kolhapur station. Rain gauge charts were analyzed in the form of annual maximum series of various durations viz. 5, 10, 15, 30, min, 1, 3, 6, 12, and 24 hrs. The plotting positions were determined by using â€œcomputing methodâ€ for the development of frequency lines. The value of â€˜aâ€™ and â€˜bâ€™ were determined by using graphical method and the values of â€˜Kâ€™ and â€˜dâ€™ were determined by least square method. The method suggested by Luzzadar was adopted for the development of Nomograph. The location constants K, a, b and d of IFD relationship for Kolhapur station for the years 1989 â€“ 2014 were found to be 3.8472, 0.1745, 0.20 and 0.7959, respectively. The nomograph was developed for Kolhapur station from IFD relationship. The per cent deviation in the values of intensities obtained from mathematical relationship of IFD equation and corresponding nomograph is in the range of (-) 3.07 to 2.09 per cent which is well below the accepted range of 20 per cent.